2015
DOI: 10.4081/ijas.2015.3646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Somatic Cell Count on Milk Yield and Composition of First and Second Lactation Dairy Cows

Abstract: This study was carried out to investigate the effect of somatic cell count (SCC) on milk yield and milk composition in first and second lactation Holstein dairy cows. Thirty cows in first lactation and 49 cows in second lactation were used in the study. Animals were 15±9.87 days in milk. Individual milk samples were collected monthly from June 2009 to March 2010, and somatic cell counts, milk protein, milk fat, lactose and milk urea-N were determined. Four SCC groups were formed for determining effect of SCC o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
39
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 11 publications
10
39
1
3
Order By: Relevance
“…The general effect of mastitis (higher SCC in the milk) is to impair milk synthesis and loosen the connections between cells (Wheelock, 1980). It was observed that SCC had a high significant effect on milk yield, milk protein, milk lactose, total solids (Cinar et al, 2015). However milk proteins synthesized and DNA in the epithelial cells in the udder decrease.…”
Section: Results Inmentioning
confidence: 96%
See 4 more Smart Citations
“…The general effect of mastitis (higher SCC in the milk) is to impair milk synthesis and loosen the connections between cells (Wheelock, 1980). It was observed that SCC had a high significant effect on milk yield, milk protein, milk lactose, total solids (Cinar et al, 2015). However milk proteins synthesized and DNA in the epithelial cells in the udder decrease.…”
Section: Results Inmentioning
confidence: 96%
“…Many studies have shown that a negative correlation between SCC in the milk and the milk protein content has been demonstrated (Cinar et al, 2015). The general effect of mastitis (higher SCC in the milk) is to impair milk synthesis and loosen the connections between cells (Wheelock, 1980).…”
Section: Results Inmentioning
confidence: 99%
See 3 more Smart Citations